276 PEDIATRIC EYE INJURIES IN ALABAMA: AN EPIDEMIOLOGIC REVIEW, 1989-2004. (1st January 2006) - Jackson, B.; Sorrentino, A.; Monroe, K.; Nichols, M.; King, W. D.
Abstract : Purpose: Children are particularly prone to injury, and eye injuries prove no exception. This study reviews a number of variables associated with serious eye injuries occurring in the pediatric population of Alabama from 1989-2004. Methods: The United States Eye Injury Registry (USEIR) is a federation of state eye injury registries, sharing a standardized data collection approach and a common database. After Institutional Review Board approval, the investigators of this study petitioned the USEIR and received the data available for the state of Alabama from January 1, 1989 through December 31, 2004. These data were analyzed using SAS, noting the following variables: patient age and race, source of injury, season of year and location, intentionality, use of protective eyewear, and sports participation. Results: From 1989-2004, 4, 334 serious eye injuries were reported in Alabama, 1, 315 in those age 18 and younger. 14.1% occurred in the 0- to 5-year age group, 40.9% in the 6- to 12-year age group, and 44.8% in the 13- to 18-year age group. 23.4% of all pediatric eye injuries occurred among those age 12-14. Patient race was reported in 83% of cases, with 55.1% of eye injuries occurring in Caucasians and 28.4% in African Americans. Other ethnicities accounted, respectively, for less than 1%, of the eye-injured patients. With respect to source, BB/pellet guns were implicated in 9.2% of injuries in 0-5 year olds, in 19.1% of injuries in 6-12 year olds, and in 12.1% of injuries in 13-18 year olds. Among the 6-12 age group, fireworks were the source of 11.7% of injuries and of 15% of injuries in the 13-18 group. 25.9% of all pediatric eye injuries occurred in January-March, 25.3% in April-June, 28.1% in July-September, and 18.8% in October-December. 80% of injuries in the 0-5 group, 68% in the 6-12 group, and 43% in the 13-18 group occurred at home. When reported, 73.9% of pediatric injuries were unintentional. In 75.4% of all pediatric injuries, no eye protection was employed, with formal protective eyewear use reported in only 0.2% of all cases. 10.4% of pediatric eye injuries were sports related, with baseball implicated in one-third of those. Conclusions: The vast majority of pediatric eye injuries occurred unintentionally, in the absence of protective eyewear, and in the setting of the home, with a slight seasonal preponderance for the summer and fall months. The role of BB/pellet guns and fireworks in these injuries is of particular concern. Eye injury awareness is lacking; thus, prevention is needed. Further research would do well to study possible preventive intervention, be that in the form of protective eyewear, education, or some combination thereof.